The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00220-018-3239-0
|View full text |Cite
|
Sign up to set email alerts
|

Bose–Einstein Condensation in a Dilute, Trapped Gas at Positive Temperature

Abstract: We consider an interacting, dilute Bose gas trapped in a harmonic potential at a positive temperature. The system is analyzed in a combination of a thermodynamic and a Gross-Pitaevskii (GP) limit where the trap frequency ω, the temperature T and the particle number N are related by N ∼ (T /ω) 3 → ∞ while the scattering length is so small that the interaction energy per particle around the center of the trap is of the same order of magnitude as the spectral gap in the trap.We prove that the difference between t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…In this system the condensate and the thermal cloud necessarily live on the same length scale and interactions between them are relevant. We prove similar statements as in the case of the trapped gas in [5], in particular, we show the existence of a BEC phase transition with critical temperature given by the one of the ideal gas to leading order.…”
Section: Background and Summarysupporting
confidence: 81%
See 3 more Smart Citations
“…In this system the condensate and the thermal cloud necessarily live on the same length scale and interactions between them are relevant. We prove similar statements as in the case of the trapped gas in [5], in particular, we show the existence of a BEC phase transition with critical temperature given by the one of the ideal gas to leading order.…”
Section: Background and Summarysupporting
confidence: 81%
“…In a more recent work [5], the trapped Bose gas at positive temperature is studied in a combination of thermodynamic limit in the trap and GP limit. It could be shown that the difference between the interacting free energy of the system and the free energy of the ideal gas is to leading order given by the minimium of the GP energy functional.…”
Section: Background and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…There exist only very limited rigorous results about the free energy of a bosonic system starting from a many-body Schrödinger Hamiltonian. In fact, in the dilute regime, the homogeneous gas in three dimensions has been treated by Seiringer [35] and Yin [38] (see also [8,9] for recent developments for the trapped and Gross-Pitaevskii cases). The lower [35] and upper bound [38] prove the free energy asymptotics F (T, ρ) = F 0 (T, ρ) + 4πa 2ρ 2 − [ρ − ρ fc ] 2 + + o(aρ 2 ) as ρa 3 → 0.…”
Section: Introductionmentioning
confidence: 99%